Broadband,polarization-insensitive,and wide-angle microwave absorber based on resistive film - 布丹丹 岳春生 张广求 胡永涛 董胜 (Chinese physics B, 2016)
A simple design of broadband metamaterial absorber（MA） based on resistive film is numerically presented in this paper.The unit cell of this absorber is composed of crossed rectangular rings-shaped resistive film,dielectric substrate,and continuous metal film.The simulated results indicate that the absorber obtains a 12.82-GHz-wide absorption from about 4.75 GHz to 17.57 GHz with absorptivity over 90% at normal incidence.Distribution of surface power loss density is illustrated to understand the intrinsic absorption mechanism of the structure.The proposed structure can work at wide polarization angles and wide angles of incidence for both transverse electric（TE） and transverse magnetic（TM） waves.Finally,the multi-reflection interference theory is involved to analyze and explain the broadband absorption mechanism at both normal and oblique incidence.Moreover,the polarization-insensitive feature is also investigated by using the interference model.It is seen that the simulated and calculated absorption rates agree fairly well with each other for the absorber.